“Poetics of Drunkenness” in Popular Literature (on Example of Ironic Detective by Darya Dontsova) - O. A. Dimitrieva (Научный диалог)
The features of verbalization of Bacchic stereotypes of the modern man on the example of the ironic detective by Daria Dontsova are considered. It is noted that the image of a drinking person is associated with certain stereotypes of appearance. The idea of the ideal / non-ideal man through verbal action to drink is revealed (in the first case, the potential-quality kind of aspect situation of repeated action, in the second - language usage kind). The author points to the programmability of the situation of drinking alcohol (there is a relatively new way of nominating such a program, similar to the conversive word formation of the English language - a composite consisting of several verbal predicates). As a result of the analysis of text fragments it is established that the assessment, in particular perceptual, is represented by visual, olfactory and other varieties and carries mainly negative connotations. The situation of wine drinking also appeals to the binary opposition light - darkness , and the state of alcoholic intoxication is associated with the last component in the pair and is interpreted as a clouding of mental abilities. It is shown that elements of medical discourse are also exploited in the artistic space of the text: the terminology of medicine ( alcoholism , alcoholic , psychology of an alcoholic , genetics ) is introduced, Bacchic situations and phenomena are creatively ironically nominated with the involvement of the vocabulary of naive medicine.